Hydrogen peroxide-induced oxidative damage and protective role of peroxiredoxin 6 protein via EGFR/ERK signaling pathway in RPE cells - Chen, Xiaodong; Tzekov, Radouil; Su, Mingyang; Zhu, Yusheng; Han, Aidong; Li, Wensheng (Frontiers in Aging Neuroscience, 2023)
Introduction Damage to retinal pigment epithelium (RPE) cells caused by oxidative stress is closely related to the pathogenesis of several blinding retinal diseases, such as age-related macular degeneration (AMD), retinitis pigmentosa, and other inherited retinal degenerative conditions. However, the mechanisms of this process are poorly understood. Hence, the goal of this study was to investigate hydrogen peroxide (H2O2)-induced oxidative damage and protective role of peroxiredoxin 6 (PRDX6) protein via EGFR/ERK signaling pathway in RPE cells. Methods Cells from a human RPE cell line (ARPE-19 cells) were treated with H2O2, and then cell viability was assessed using the methyl thiazolyl tetrazolium assay. Cell death and reactive oxygen species (ROS) were detected by flow cytometry. The levels of PRDX6, epidermal growth factor receptor (EGFR), P38 mitogen-activated protein kinase (P38MAPK), c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK) were detected by Western blot assay. PRDX6 and EGFR were also detected via immunofluorescence staining. Results Our results show that H2O2 inhibited cell viability, induced cell death, and increased ROS levels in ARPE-19 cells. It was also found that H2O2 decreased the levels of PRDX6, EGFR, and phosphorylated ERK but increased the levels of phosphorylated P38MAPK and JNK. PRDX6 overexpression was found to attenuate H2O2-induced inhibition of cell viability and increased cell death and ROS production in ARPE-19 cells. PRDX6 overexpression also increased the expression of EGFR and alleviated the H2O2-induced decrease in EGFR and phosphorylated ERK. Moreover, inhibition of epidermal growth factor-induced EGFR and ERK signaling in oxidative stress was partially blocked by PRDX6 overexpression. Discussion Our findings indicate that PRDX6 overexpression protects RPE cells from oxidative stress damage caused by decreasing ROS production and partially blocking the inhibition of the EGFR/ERK signaling pathway induced by oxidative stress. Therefore, PRDX6 shows promise as a therapeutic target for the prevention of RPE cell damage caused by oxidative stress associated with retinal diseases.